Regulation of angiotensin II receptors in the rat adrenal cortex by dietary electrolytes. - Douglas, J (1976)
The binding affinity and concentration of specific angiotensin II receptor sites of rat adrenal cortical cells and homogenates were determined after 1 and 6 wk of altered sodium and potassium intake. Sodium deprivation caused marked increases in plasma renin, blood angiotensin II, and plasma aldosterone, and was accompanied by a significant increase (+74%) in the number of specific angiotensin II receptor sites per adrenal cortical cell. High potassium intake was followed by increased serum potassium and markedly elevated plasma aldosterone, with subnormal levels of renin and angiotensin II and a 170% increase in the number of angiotensin II receptors per cell after 1 wk. Sodium loading and potassium deprivation were followed by the opposite effect upon adrenal receptors, with reduction of the angiotensin II-binding capacity. None of the dietary electrolyte changes were accompanied by an ancrease in receptor affinity above the control value of 2 nM-1. A decrease in receptor affinity was noted after 6 wk of either low sodium or low potassium intake, when the renin and angiotensin II levels were increased by 104-129%. The adrenals of normal rats infused acutely with synthetic angiotensin II, or anesthetized with ether or sodium pentobarbital, which markedly increased plasma renin activity, contained fewer angiotensin receptors. These reductions in binding site concentration were not accompanied by changes in affinity and were attributed to occupancy by angiotensin II. These studies have demonstrated that chronic changes in sodium or potassium balance and acute changes in blood angiotensin II levels can exert modulating effects upon the adrenal content and/or affinity of specific receptor sites for angiotensin II.